Performance evaluation of VLC system using new modulation approach - M. Nawawi, N.; M. S., Anuar; N. Junita, M.; R. Abdullah, S. (Institute of Advanced Engineering and Science, 2019)
We propose a modified OFDM modulation based on multiband scheme for visible light communications (VLC) system. The method called catenated-OFDM VLC system can efficiently boost the propagation distance and combat multipath induced the inter symbol interference and inter carrier interference. Design parameters such as number of optical bands, input power, distance and data rate are varied to see their effect on the system performances. Simulation analysis is done using Optisys software Ver. 11.0. The results show that the proposed system offers a good performance at longer transmission distance of 12 m for input power of 2 dBm in case of Band = 3 with 10 Gbps data rate. BER curves also indicates that the proposed system can be operated at very high data rate of 15 Gbps. This exhibits the ability of the proposed system to be one of the candidate for future optical wireless communication system.